2021
DOI: 10.1007/s12015-021-10239-2
|View full text |Cite
|
Sign up to set email alerts
|

c-MYC Triggers Lipid Remodelling During Early Somatic Cell Reprogramming to Pluripotency

Abstract: Metabolic rewiring and mitochondrial dynamics remodelling are hallmarks of cell reprogramming, but the roles of the reprogramming factors in these changes are not fully understood. Here we show that c-MYC induces biosynthesis of fatty acids and increases the rate of pentose phosphate pathway. Time-course profiling of fatty acids and complex lipids during cell reprogramming using lipidomics revealed a profound remodelling of the lipid content, as well as the saturation and length of their acyl chains, in a c-MY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“… 19 , 45 Our previous study has indicated that LPLUNC1 can upregulate PHB1 expression and enhance its stabilization by reducing its ubiquitination degradation to attenuate the NF‐kB signaling, 18 supporting the notion that PHB1 can affect multiple signal pathways to inhibit tumor cell proliferation. 19 , 24 , 29 , 41 In this study, we found that LPLUNC1 upregulated PHB1 protein expression and promoted phosphorylated PHB1 nuclear translocation by upregulating the expression of 14‐3‐3σ, an endoplasmic reticulum lipid raft protein. 34 , 46 Our data indicated that PHB1 Tyr259 phosphorylation was critical for its action in decreasing glycolysis and increasing OXPHOS‐related protein expression in NPC cells.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“… 19 , 45 Our previous study has indicated that LPLUNC1 can upregulate PHB1 expression and enhance its stabilization by reducing its ubiquitination degradation to attenuate the NF‐kB signaling, 18 supporting the notion that PHB1 can affect multiple signal pathways to inhibit tumor cell proliferation. 19 , 24 , 29 , 41 In this study, we found that LPLUNC1 upregulated PHB1 protein expression and promoted phosphorylated PHB1 nuclear translocation by upregulating the expression of 14‐3‐3σ, an endoplasmic reticulum lipid raft protein. 34 , 46 Our data indicated that PHB1 Tyr259 phosphorylation was critical for its action in decreasing glycolysis and increasing OXPHOS‐related protein expression in NPC cells.…”
Section: Discussionmentioning
confidence: 58%
“… 28 In contrast, c‐Myc is highly expressed in a variety of tumors and can enhance glycolysis and activation of the PPP in different types of tumor cells. 18 , 29 Previous studies have shown that PHB1 can downregulate the expression of c‐Myc in tumor cells. 30 We hypothesize that LPLUNC1 may modulate p53 and c‐Myc expression by enhancing PHB1 to regulate glucose metabolism in NPC cells.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, c-Myc has been reported to inhibit oxidative stress during ventricular remodeling of rats with myocardial infarction ( 54 ). c-Myc may restore appropriate levels of antioxidant proteins to ensure optimal mitochondrial function while maintaining ROS levels ( 55 ). Kfoury et al proposed that ROS levels are significantly increased in melanoma cells following knockdown of c-Myc expression, which promotes the induction of apoptosis of melanoma cells ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…After completing MET, cells increase their proliferation rate, suppressing proapoptotic and senescence factors, which are required for extensive epigenetic modification ( Marion et al, 2009a ; Hong et al, 2009 ; Utikal et al, 2009 ; Yunusova et al, 2017 ). MET also leads to the upregulation of genes involved in cell proliferation, metabolism, and cytoskeletal organization—c-Myc, MycN, KLF4, and Pdzk1 ( Prieto et al, 2021 ). At this stage, cells lack DNA methylation, and active histone modifications mediate the suppression of cell type-specific genes ( Polo et al, 2012 ).…”
Section: Main Characteristics Of the Stages Of Reprogramming Toward P...mentioning
confidence: 99%